Challenges to the improvement of obstetric care in maternity hospitals of a large Brazilian city: an exploratory qualitative approach on contextual issues - Margareth Crisóstomo Portela; Sheyla Maria Lemos Lima; Lenice Gnocchi da Costa Reis; Mônica Martins; Emma-Louise Aveling (BMC, 2018)
Abstract Background Maternal morbidity and mortality are still serious public health concerns in Brazil, and access to quality obstetric care is one critical point of this problem. Despite efforts, obstetric care quality problems and sub-optimal/poor outcomes persist. The study aimed to identify contextual elements that would potentially affect the implementation of an obstetric care quality improvement intervention. Methods A qualitative study was conducted in three public maternity hospitals of a large Brazilian city, with high annual volume of births and buy-in from high-level managers. Individual interviews with doctors and nurses were conducted from July to October 2015. Semi-structured interviews sought to explore teamwork, coordination and communication, and leadership, being open to capture other contextual elements that could emerge. Interviews were recorded and transcribed, and the categories of analysis were identified and updated based on the constant comparative method. Results Twenty-seven interviews were carried out. Extra-organizational context concerning the dependence of the maternity hospitals on primary care units, responsible for antenatal care, and on other healthcare organizations' services emerged from interviews, but the main findings of the study centered on intra-organizational context with potential to affect healthcare quality and actions for its improvement, including material resources, work organization design, teamwork, coordination and communication, professional responsibility vis-à-vis the patient, and leadership. A major issue was the divergence of physicians' and nurses' perspectives on care quality, which in turn negatively affected their capacity to work together. Conclusion Overall, the findings suggest that care on the maternity hospitals was fragmented and lacked continuity, putting at risk the quality. Redesigning work organization, promoting conditions for multi-professional teamwork, better communication and coordination, improving more systemic accountability/lines of authority, and investing in team members' technical competence, and fitness of organizational structures and processes are all imbricated actions that may contribute to obstetric care quality improvement.